MOTIVATION OF ANEUK JAMEE TRIBES CIVIL SERVANT IN INDONESIAN LANGUAGE SELECTION IN TAPAK TUAN CITY - Saratul Idami; Saifuddin Bantasyam (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
The social strata is the level and the different hierarchy between groups of people in a society or culture and its role to motivation in language selection in the local community Aneuk Jamee tribe is very large. This study aims to describe the role of social strata against motivation in language selection in the local community Aneuk Jamee tribe in Tapak Tuan city. The theory used is the theory of Symbolic Interaction by Herbert Blumer. The research method used is qualitative explanative descriptive approach by conducting in dept interview as data collection technique. The results show that economic progress elevates the position of a language. Indonesian language attracts many people to master and use Indonesian language as the main language, so that the local language or Jamee language is not used anymore in communicating because the Indonesian language is used as a condition that must be met by someone to communicate in the environment. The role of strata in the Aneuk Jamee tribe greatly influences the language. Status as civil servants in society has a high social strata. Because of its status as a civil servant it will affect the language. The language used in the work environment is Indonesian which allows a person to be motivated to teach his/her children using Indonesia language, because they consider that the language is more valuable or elite, more modern and also has a greater scope in interacting. Keywords: Social Strata, Language, Aneuk Jamee Tribe